The Drought Response of Eastern US Oaks in the Context of Their Declining Abundance. (25th January 2022) - Novick, Kimberly; Jo, Insu; D'Orangeville, Loïc; Benson, Michael; Au, Tsun Fung; Barnes, Mallory; Denham, Sander; Fei, Songlin; Heilman, Kelly; Hwang, Taehee; Keyser, Tara; Maxwell, Justin; et al.
Abstract: The oak (Quercus) species of eastern North America are declining in abundance, threatening the many socioecological benefits they provide. We discuss the mechanisms responsible for their loss, many of which are rooted in the prevailing view that oaks are drought tolerant. We then synthesize previously published data to comprehensively review the drought response strategies of eastern US oaks, concluding that whether or not eastern oaks are drought tolerant depends firmly on the metric of success. Although the anisohydric strategy of oaks sometimes confers a gas exchange and growth advantage, it exposes oaks to damaging hydraulic failure, such that oaks are just as or more likely to perish during drought than neighboring species. Consequently, drought frequency is not a strong predictor of historic patterns of oak abundance, although long-term climate and fire frequency are strongly correlated with declines in oak dominance. The oaks' ability to survive drought may become increasingly difficult in a drier future.